A TaqMan real time probe assay for specific detection and quantification of lapinized vaccine strain of classical swine fever virus - JOHN, JENY K; ANOOPRAJ, R; TOMAR, NEELAM; SAIKUMAR, G (The Indian Journal of Animal Sciences, 2017)
Classical swine fever (CSF) is a highly contagious viral disease having a tremendous socio-economic impact. In CSF endemic countries such as India, control strategies depend heavily on the use of a live attenuated vaccine. The persistence of vaccine virus in tissue/blood of vaccinated animals may interfere with the diagnosis when RT-PCR assay is used for CSF diagnosis. A TaqMan based real-time RT-PCR assay was developed with primers and probe targeting the NS5B region of the lapinized CSFV (vaccine strain) used in India for detection and quantification of lapinized CSFV. The real-time TaqMan RT-PCR assay presented in the current study provided a rapid, specific and sensitive diagnostic tool for the detection of LCSFV and for quantification of virus load in various organs. This real time RT-PCR assay can differentiate the infected from vaccinated animals and quantification assay can be used for post-vaccination studies.